2021
DOI: 10.7251/agreng1902043m
|View full text |Cite
|
Sign up to set email alerts
|

Micronutritient Variability in Maize Inbred Lines

Abstract: Development of micronutrienten riched staple plant foods through plant breeding holds promise for sustainable and cost-effective food-based solutions to combat micronutrient deficiencies. The first step in this process is screening aviable germplasm for micronutritient content, so the aim of this study was determination of carotenoids and tocopherols content in set of maize inbred lines. Carotenoids (lutein, zeaxanthin and β-carotene) and tocopherols (α, β+γ and δ) content in 101 maize inbred lines with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…As reported by Mladenović Drinić et al (2019), among 101 inbreds with different kernel types and colour, lutein+zeaxanthin and β-carotene had respective mean contents of 31.34 and 8.72 μg/g. The range of β-carotene content was 1.20 to 39.37 μg/g.…”
Section: O N L I N E F I R S Tmentioning
confidence: 56%
See 2 more Smart Citations
“…As reported by Mladenović Drinić et al (2019), among 101 inbreds with different kernel types and colour, lutein+zeaxanthin and β-carotene had respective mean contents of 31.34 and 8.72 μg/g. The range of β-carotene content was 1.20 to 39.37 μg/g.…”
Section: O N L I N E F I R S Tmentioning
confidence: 56%
“…According to Kaur, Singh and Sharma (2019), compared to regular maize, quality protein maize (QPM) refined flour has higher levels of fat (3.90%), protein (10.04%), and carbohydrates (74.83%). Milašinović-Šeremešić, Radosavljević, Srdić, Tomičić and Đuragić (2019) previously reported average oil content of different maize hybrids amounted to 4.14%. Albeit, the oil content determined in the investigated wholegrain maize flours from inbred lines exceeded the maximal allowed values prescribed by the Serbian regulation on the quality requirements for milled maize products (Pravilnik, 2018), namely for wholemeal (4%) and refined maize flour (3%) which is obtained by dry a grinding process (after removal of the grain pericarp, and germ in which most lipids are located).…”
Section: O N L I N E F I R S Tmentioning
confidence: 97%
See 1 more Smart Citation
“…The carotenoids were determined only in wholegrain flour produced from yellow kernel popping maize (26.5±1.2 mg βCE/kg), while tocopherols were detected in the red dent and blue popping maize wholegrain flours (Table 2). A study conducted by Mladenović-Drinić et al (2019) also reported that carotenoids were not present in the investigated white maize inbred lines which was explained by the presence of a recessive gene that controls the first step in the carotenoid synthesis pathway. Similarly, these researchers found that standard yellow/orange kernel dent and popcorn genotypes had a higher content of carotenoids, predominantly β-carotene, lutein, and zeaxanthin.…”
Section: Cge -Cyanidin-3-glucoside Equivalent; βCe -β-Carotene Equiva...mentioning
confidence: 96%
“…Maize grain is a significant source of vitamin B1, B2, B5, B12, and vitamin E, β-carotene -a provitamin of vitamin A, also has high phenolic content compounds (among other anthocyanins), which have the role of antioxidants as well as minerals potassium (K) and magnesium (Mg) (Farré Martinez, 2012). Apart from the significant nutritional value the bioactive components of the maize grain can provide both health and economic benefits, which potentially could be utilized to add even more value to this grain (Mladenović-Drinić et al, 2019). This study aimed to examine the chemical composition of differently colored maize kernel wholegrain flours to asses and compare their nutritional potentials.…”
Section: Introductionmentioning
confidence: 99%